Identification and characterization of a Bacillus methylotrophicus strain with high flocculating activity. Issue 111 (26th October 2015) - Li, Tan; Wang, Jing; Wei, Xiaoling; Zhao, Hong-Yi; Zhao, Zhong-Xing; Liu, Hai-Bo
Abstract : A novel bioflocculant-producing strain C412 was derived from Bacillus methylotrophicus . The bioflocculant is pH tolerant and thermostable; charge neutralization and bridging are the main flocculation mechanism. Abstract : A novel bioflocculant-producing strain C412 was derived from Bacillus methylotrophicus . The bioflocculant secreted by strain C412 is composed of 57.30% polysaccharides and 1.70% protein. The results of GPC indicated that the average molecular weight of the bioflocculant was 3.47 × 10 5 . A maximum flocculating activity of 98.27% was achieved using an optimized culture medium, identified by response surface methodology, containing (per liter) soluble starch (19.73 g), beef extract (1.35 g), (NH4 )2 SO4 (3.05 g), NaCl (1.00 g), KH2 PO4 (2.00 g), K2 HPO4 (5.00 g), and MgSO4 (0.05 g) at pH 7.63. The bioflocculant is thermostable over a broad temperature range (4 °C to 60 °C) and has a wide pH stability (4 to 13). Batch fermentation of strain C412 in high cell density cultures showed shorter generation times in a 1.5 L fermentor (2–6 h) than in a shake-flask (13–17 h). The relationship between the expression levels of katE, pepT, and scrR and the flocculating activity was established. Furthermore, a two-step flocculation mechanism ( i.e., charge neutralization and bridging) was proposed based on zeta potential analysis.